Namibia : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper examines macro-financial risks associated with housing boom in Namibia. Namibia has enjoyed stable and steady progress in financial sector developments, but vulnerabilities might have built up. The recent evolution of Namibia's housing prices raises a question as to whether the prices reflect economic fundamentals. Overall, estimates based on cross-country evidence of countries that experienced a boom-bust episode in the housing sector suggest that Namibia's real economic growth could be 3 to 27 percentage points lower than under the baseline scenario over a three-year period. Under the most adverse scenario, in particular, GDP is expected to contract 9.9 percent in real terms over the three-year projection period.